2021
DOI: 10.7554/elife.62001
|View full text |Cite
|
Sign up to set email alerts
|

Spinal lumbar dI2 interneurons contribute to stability of bipedal stepping

Abstract: Peripheral and intraspinal feedback is required to shape and update the output of spinal networks that execute motor behavior. We report that lumbar dI2 spinal interneurons in chicks receive synaptic input from afferents and premotor neurons. These interneurons innervate contralateral premotor networks in the lumbar and brachial spinal cord, and their ascending projections innervate the cerebellum. These findings suggest that dI2 neurons function as interneurons in local lumbar circuits, are involved in lumbo-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Since we have shown that LDPNs are negative for GlyT2 and ChAT and dI4 and dIL A INs are dorsal neurons ( Glasgow et al, 2005 ; Pillai et al, 2007 ) expression of Lhx1 would point to cervical LDPNs belonging to either the V0 V or dI2 class. In fact, it has very recently been shown that dorsally derived excitatory dI2 INs migrate to this region in the chick spinal cord and have divergent axons along the length of the cord and to the cerebellum ( Haimson et al, 2021 ). While these neurons are not premotor in the chick ( Haimson et al, 2021 ), it is possible that they are in the mouse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we have shown that LDPNs are negative for GlyT2 and ChAT and dI4 and dIL A INs are dorsal neurons ( Glasgow et al, 2005 ; Pillai et al, 2007 ) expression of Lhx1 would point to cervical LDPNs belonging to either the V0 V or dI2 class. In fact, it has very recently been shown that dorsally derived excitatory dI2 INs migrate to this region in the chick spinal cord and have divergent axons along the length of the cord and to the cerebellum ( Haimson et al, 2021 ). While these neurons are not premotor in the chick ( Haimson et al, 2021 ), it is possible that they are in the mouse.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has very recently been shown that dorsally derived excitatory dI2 INs migrate to this region in the chick spinal cord and have divergent axons along the length of the cord and to the cerebellum ( Haimson et al, 2021 ). While these neurons are not premotor in the chick ( Haimson et al, 2021 ), it is possible that they are in the mouse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From work in the cat, it has become clear that sensory inputs are important for initiating and maintaining an appropriate locomotor rhythm by regulating phase changes during stepping and modulating the amplitude of motor output ( Stuart and Hultborn, 2008 ). Dorsal interneurons also project supraspinally and receive descending input to regulate descending pathways ( Bourane et al, 2015 ; Haimson et al, 2021 ). Since dorsal spinal interneurons regulate these sensory pathways, one can be certain that they will exhibit large differences between water- and land-based animals, consistent with current observations of dorsal subtype radiation from zebrafish to mouse ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, very little is known about dI2 anatomy or function. A recent study in chick however, showed that dI2 neurons at limb levels receive sensory and premotor interneuron input, and project to the cerebellum ( Haimson et al, 2021 ). Silencing of dI2 neurons in chick results in abnormal hindlimb stepping ( Haimson et al, 2021 ), implicating them in the high-level coordination of limb movement.…”
Section: Other Dorsal Interneuronsmentioning
confidence: 99%